Fatores de decisão da adoção do gás natural na geração de energia elétrica em pequena escala em postos de combustíveis: um estudo de anális de decusão usando o processo de hierarquia analítica AHP - Sousa, ítalo Raimundo de (2007)
A modeling of criterias and alternatives is through and applied a questionnaire based on method AHP to proprietors of gas stations. The considered alternatives had been the maintenance of the current state with electric energy of the deliverer and the generation in small scale based on the natural gas. The used criteria had been Cost of the Investment, Final Cost of the Energy, Operational cost, Ambient Benefits, Risk and Variation of Costs. The study it was carried through in the city of Natal, RN in ranks that make use of the natural as for resale, where the generation alternative on the basis of the available gas is present. The main results evidence in a dimension the viability of use of method AHP with questionnaire by means of validation of the judgments with analysis of variance beyond proper the normal mechanisms of analysis of consistency to the method. The main results of the analysis help to show that in this in case that the profile of models of criteria and judgments of the actors is similar, with the final evidence of that it has a dominance of the maintenance of the energy of the deliverer. The main criterion to influence this decision was the risk